Synchronization properties of self-sustained mechanical oscillators - Arroyo, Sebastián Ismael; Zanette, Damian Horacio (Amer Physical Soc, 2013)
Fil: Arroyo, Sebastián Ismael. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina